Estimation and improvement of conservation of the biological diversity of the Caspian for the national and international ecological problems solution - B. N. Morozov; G. M. Abdurakhmanov (Юг России: экология, развитие)
The work is an analysis of biological diversity, for stable functioning of biosphere sufficient. Acts for the decision of national, regional and transboundary environmental problems are discussed.